Pulmonary aspergillosis in critically ill patients with Coronavirus Disease 2019 (COVID-19). (10th September 2020) - Dupont, Damien; Menotti, Jean; Turc, Jean; Miossec, Charline; Wallet, Florent; Richard, Jean-Christophe; Argaud, Laurent; Paulus, Sylvie; Wallon, Martine; Ader, Florence; Persat, Florence
Abstract: Occurrence of putative invasive pulmonary aspergillosis was screened in 153 consecutive adult intensive care unit (ICU) patients with respiratory samples addressed for mycological diagnosis during a 6-week period at the emergence of coronavirus disease 2019 (COVID-19) pandemic. Positive severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) polymerase chain reaction (PCR) was observed for 106 patients (69.3%). Nineteen of them (17.9%) with positive Aspergillus results were considered as having putative invasive pulmonary aspergillosis. These observations underline the risk of pulmonary aspergillosis in COVID-19 patients, even in patients not previously known to be immunosuppressed, advocating active search for Aspergillus infection and prompt antifungal treatment. Standardized surveillance protocols and updated definitions for ICU putative invasive pulmonary aspergillosis are needed. Lay Abstract: Adult ICU patients with respiratory samples addressed for mycological diagnosis were screened during the emergence of COVID-19 pandemic. Positive SARS-CoV-2 PCR was observed for 106 patients, nineteen of them (17.9%) having aspergillosis. This underlines the risk of aspergillosis in COVID-19 patients.